2020
DOI: 10.3892/ol.2020.11256
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bcl‑2 on drug resistance in breast cancer polyploidy‑induced spindle poisons

Abstract: Spindle poisons are chemotherapeutic drugs used in the treatment of malignant tumors; however, numerous patients develop resistance following chemotherapy. The present study aimed to induce polyploidy in breast cancer cells using the spindle poison nocodazole to investigate the mechanism of polyploid-induced tumor resistance. It was revealed that the spindle poison nocodazole induced apoptosis in HCC1806 cells but also induced polyploidy in MDA-MB-231 cells. The drug sensitivities of the polyploid MDA-MB-231 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…It was demonstrated that ruxolitinib partly suppressed CRC cell proliferation by inducing apoptosis through activating the intrinsic pathway. Bcl-2 family proteins that are key mediators of the intrinsic apoptosis pathway were screened out ( 25 , 26 ). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that ruxolitinib partly suppressed CRC cell proliferation by inducing apoptosis through activating the intrinsic pathway. Bcl-2 family proteins that are key mediators of the intrinsic apoptosis pathway were screened out ( 25 , 26 ). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As well, the top central genes of the constructed network typically attributed to nuclear process. According to our previous studies indicating the importance of central genes in promotion of cellular phenotype [45,46], we think that the central nodes as well as genes in the densely-connected modules which belonged to chromatid segregation, microtubule polymerization and membrane budding, indicate the key role of nuclear processes and polyploidy in cancer resistance [47][48][49][50][51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of these proteins can result from mutations in or upregulation of antiapoptotic genes, leading to resistance to chemotherapy. Numerous studies have indicated that increased expression of Bcl‐2 or an increase in the Bcl‐2/BAX ratio is strongly associated with poor clinical outcomes, rendering cancer cells resistant to chemotherapy and radiation both in vitro and in vivo (Kaloni et al, 2023; Kapoor et al, 2020; Yuan et al, 2020). Patients with Bcl‐2‐positive malignancies are at a higher risk of treatment failure and have a poor prognosis (Makino et al, 2018; Michaud et al, 2009).…”
Section: Bcl‐2 Family Proteins In Cancersmentioning
confidence: 99%